Reasons of interfaith marriage actors from the perspective of Islamic Law (case study of interfaith marriage in New Sorowajan Hamlet, Village Banguntapan, Banguntapan Distric, Bantul) - Ahmad Afandi (Fak. Syari'ah UIN SUKA, 2010)
why/sgh.c1